Isolation and functional characterization of a basic phospholipase A2 from Colombian Bothrops asper Venom (2014)
ABSTRACT: Background: Snakebites represent a relevant public health issue in many regions of the world, particularly in tropical and subtropical countries of Africa, Asia, Latin America and Oceania. Snake venoms are complex mixtures of toxic enzymes and proteins, where the most important and abundant muscle-damaging components in snake venoms are phospholipases A2 (PLA2s). Objective: Isolate and characterize a phospholipase A2 from Colombian Bothrops asper venom, in order to obtain information about venom composition of this species. Materials and methods: Cation-exchange chromatogra phy followed by reverse phase HPLC were used to purify the protein. Mass spectrometry was used to determine its molecular mass. Biochemical characterization was performed using a synthetic substrate (4-nitro-3-octanoyloxy-benzoic acid). Myotoxic and edema-inducing activity of toxin were tested in mice, by measuring the plasma creatine kinase activity and footpad diameter, respectively. Moreover, cytotoxic activity was examined to murine skeletal muscle C2C12 myoblasts and myotubes. Results: A PLA2 of Bothrops asper venom from Colombia (BaspCol-PLA2) was purified. Its molecular mass was 13974.6 Da. The enzyme hydrolyzed a synthetic substrate with a KM of 3.11 mM and a VMax of 4.47 nmol/min, showing maximum activity at 40 °C and at pH 8.0. The PLA2 required Ca2+ for activity. The addition of Mg2+, Cd2+, Mn2+ and Zn2+ (10mM) in the presence of low Ca2+ concentration (1mM) decreased the enzyme activity. The substitution of Ca2+ by mentioned divalent cations also reduced the activity to levels similar to those in the absence of Ca2+. Three internal fragments (CCFVHDCCYGK, AAAI/ LCFRDNI/LNTYNDKK, DAAI/LCFR) identified by a mass spectrometry analysis showed similarity with previously reported B. asper PLA2s. In mice, BaspCol-PLA2 induced a conspicuous local myotoxic effect and moderate footpad edema. In vitro, this enzyme induced cytotoxic effect on both myoblasts and myotubes. Additionally, it was classified as weakly anticoagulant PLA2, showing this effect at concen trations between 3 and 10 μg/mL when using human plasma. Conclusions: A PLA2 was purified and named BaspCol-PLA2, this enzyme displayed catalytic activity and molecular mass of 13974.6 Da. The toxin showed myotoxic, edema-forming, anticoagulant and cytotoxic activities.